2013
DOI: 10.1186/1479-5876-11-111
|View full text |Cite
|
Sign up to set email alerts
|

SATB1 is overexpressed in metastatic prostate cancer and promotes prostate cancer cell growth and invasion

Abstract: BackgroundSpecial AT-rich sequence binding protein 1 (SATB1) is a nuclear factor that functions as the global chromatin organizer to regulate chromatin structure and gene expression gene expression. SATB1 has been shown to be abnormally expressed in various types of cancer. However, the expression and role of SATB1 in prostate cancer remain unclear.Methods120 cases of prostatic carcinoma and 60 cases of benign prostate hyperplasia were analyzed for SATB1 expression by immunohistochemistry. LNCaP, DU-145, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 18 publications
5
64
1
Order By: Relevance
“…SATB1 as a MAR-binding protein regulates the genes by folding chromatin into loop domain [8]. It was found to regulate gene expression in thymocytes and pre B-cells [9], but recent studies have shown that SATB1 promotes tumor growth and metastasis through chromatin gene recombination in many neoplasms such as breast, gastrointestinal tract (predominantly colorectal region), liver, laryngeal, lung, thyroid, urinary bladder, ovarian and prostate cancers, melanomas, osteosarcomas, gliomas and some types of leukemias [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, except SATB1 involvement in tumor progression by its mRNA and protein overexpression in some cancers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SATB1 as a MAR-binding protein regulates the genes by folding chromatin into loop domain [8]. It was found to regulate gene expression in thymocytes and pre B-cells [9], but recent studies have shown that SATB1 promotes tumor growth and metastasis through chromatin gene recombination in many neoplasms such as breast, gastrointestinal tract (predominantly colorectal region), liver, laryngeal, lung, thyroid, urinary bladder, ovarian and prostate cancers, melanomas, osteosarcomas, gliomas and some types of leukemias [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, except SATB1 involvement in tumor progression by its mRNA and protein overexpression in some cancers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has also been reported in other types of tumors, such as liver, prostate, ovarian, gastric, and kidney tumors. [8][9][10][11][12] We further analyzed the expression of SATB1 in corresponding lymph node metastases, and we found that SATB1 expression was remarkably higher in lymph node metastases than in CRC primary lesions. These results suggest that SATB1 plays a crucial role in promoting tumor growth, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, SATB1 was initially found to have a role in promoting growth and metastasis in breast cancer. 7 It has subsequently been found to correlate with poor prognosis in several other forms of tumor, such as liver cancer, 8 prostate cancer, 9 ovarian cancer, 10 gastric cancer, 11 and renal cell carcinoma. 12 As such, SATB1 is considered to be a new type of key oncogene regulator.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of SATB1 has been examined in esophageal adenocarcinoma and is an independent prognostic factor (20). In several types of cancer, including laryngeal squamous cell carcinoma, endometrial cancer, hepatocellular cancer and lung cancer, high expression of SATB1 promotes tumor growth and metastasis, and is a negative prognostic factor (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). SATB1 can regulate the expression of >1,000 genes involved in the processes of DNA organization, proliferation and apoptosis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…SATB1 can regulate gene expression by folding chromatin into loop domains and tethering DNA domains to the SATB1 network structure (7,8). Under normal conditions, SATB1 is expressed at low levels in cells and tissues, but is overexpressed in a variety of malignant tumors, including laryngeal squamous cell carcinoma, endometrial cancer, hepatocellular carcinoma, rectal cancer, cutaneous malignant melanoma, gastric cancer, prostate cancer, lung cancer and cutaneous T-cell lymphoma (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The expression of SATB1 has been examined in esophageal adenocarcinoma and is an independent prognostic factor (20).…”
Section: Introductionmentioning
confidence: 99%